Optimization of nano-silica's addition in cement mortars and assessment of the failure process using acoustic emission monitoring. (30th October 2016) - Barkoula, N.-M.; Ioannou, C.; Aggelis, D.G.; Matikas, T.E.
Graphical abstract: Highlights: Nano-silica's addition results in enhanced mechanical properties and AE activity. "Wet" is more effective process and offers stable properties at limited mixing time. "Dry" mixing procedure can be used only in conjunction with superplasticizers. A more tortuous path of the crack is found after the addition of nano-silica. Abstract: The objective of this work was to optimize nano-silica's addition in cement mortars using different mixing procedures. Nano-silica was either dispersed in water using sonication or directly added into cement and mixed using a rotary mixer. The fresh and hardened properties of nano-silica modified mortars were defined while acoustic emission (AE) activity was monitored and correlated with the failure processes. The addition of nano-silica resulted in 25–35% increase of the mechanical properties accompanied with simultaneous influence on the failure process as indicated by AE. Sonication was beneficial leading in stable mechanical properties at limited mixing duration.